Remote sensing and its application in agricultural pest management - Acharya, MC; Thapa, RB (Journal of Agriculture and Environment, 2015)
Agricultural production is significantly affected by biotic- living organisms, such as predator, parasites, pathogens and abiotic factors, like temperature, humidity, rainfall etc. To manage the pests, monitoring and forecasting has been an integrated part of the crop production system in developed countries. In recent years, remote sensing has become popular in pest monitoring, yield forecasting, and early warning to crop growers for timely management of potential pests in agriculture. This paper highlights basic functioning of remote sensing and its application in agriculture with main emphasis on pest management.